2015
DOI: 10.1021/jp509334u
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Chemical Study of the Effect of Precursor Stereochemistry on Dissociative Chemisorption and Surface Redox Reactions During the Atomic Layer Deposition of the Transition Metal Copper

Abstract: Using quantum chemical calculations, we investigate surface reactions of copper precursors and diethylzinc as the reducing agent for effective Atomic Layer Deposition (ALD) of Cu. The adsorption of various commonly used Cu (II) precursors is explored. The precursors vary in the electronegativity and conjugation of the ligands and flexibility of the whole molecule. Our study shows that the overall stereochemistry of the precursor governs the adsorption onto its surface. Formation of different Cu (II) /Cu (I) /… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 66 publications
2
12
0
Order By: Relevance
“…21 The same redox behavior is computed to occur during the adsorption of other Cu(ii) precursors based on pyrrolylaldehyde N-isopropyl-2-pyrrolylaldiminate and 4N-(ethylamino)pent-3-en-2-onate ligands, as well as acac and dmap. 22 Charge is delocalized between the Cu precursor and the bare copper surface, indicating metallic bonding as the precursor densifies to the surface. It is computed that adsorption is stronger for those precursors with less steric hindrance, flexible ligands, and a planar geometry, because this allows access to surface atoms and the formation of strong metallic bonds.…”
Section: Redox Adsorption Of Metal Precursormentioning
confidence: 99%
“…21 The same redox behavior is computed to occur during the adsorption of other Cu(ii) precursors based on pyrrolylaldehyde N-isopropyl-2-pyrrolylaldiminate and 4N-(ethylamino)pent-3-en-2-onate ligands, as well as acac and dmap. 22 Charge is delocalized between the Cu precursor and the bare copper surface, indicating metallic bonding as the precursor densifies to the surface. It is computed that adsorption is stronger for those precursors with less steric hindrance, flexible ligands, and a planar geometry, because this allows access to surface atoms and the formation of strong metallic bonds.…”
Section: Redox Adsorption Of Metal Precursormentioning
confidence: 99%
“…Gas-phase energetics are used to screen possible surface intermediates, [ 80 ] which are then used in calculations of reaction pathways on a cluster model surface. [ 81 ] The role of precursor stereochemistry is examined and it is found that sterically hindered precursors have less chance of adsorption onto the surface. Pathways to incorporation of Zn impurity are identifi ed, explaining the experimental results.…”
Section: Progress Reportmentioning
confidence: 99%
“…Recently, quantum chemistry (QC), in particular density functional theory (DFT) calculations, has become a powerful tool to explicit the ALD chemistry at an atomic scale. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] Dey et al 31 investigated the transmetalation reactions in Cu ALD using diethylzinc as the reducing agent, following experiments by Lee et al 8 Lin et al 32 have investigated the competition between ligand-exchange reactions and surface decomposition of Cu(acac) 2 on a Si(100)-2 Â 1 surface. More recently, we have studied the surface reactions of ( n Bu 3 P) 2 Cu(acac) and Cu(acac) 2 precursors on a Ta(110) surface.…”
Section: Introductionmentioning
confidence: 99%